Mental health and its Impact on judges during the course of a criminal case – Statistical Psychological Study – - Mohammed, Eiman Abd Elrsol; Saad, Sofian Abuelbacher Adam; Mohmed, Nedal Abd Alhadi (Journal of Educational and Psychological Sciences, 2021)
The study aims to identify the mental health of the judges during the criminal proceedings in addition to the main factors that affect it. The descriptive analytical method was used depending on the analysis of variance as suitable tools to reach the relevant results. The sample of the study consists of judges, where the number of (30) judges were randomly selected. The study tools were the mental health scale, interview and observation. The study reached the following results (I.e. all variables relations have been tested at a significance level 0.05): There is a significant effect of the social status on the mental health of the judges during the course of criminal case, there is no significant effect of the age on the mental health of the judges during the course of criminal case, there is no significant effect of the years of experience on the mental health of judges during the course of criminal case, there is a significant effect of the numbers of training courses received by judges on mental health during the course of criminal case, and the mental health of judges during the course of criminal case is low.
Keywords: Mental health; criminal case; judges; South Darfur State